부식산 함유 액상비료 시비에 따른 크리핑 벤트그래스의 생육과 품질 변화 - 김영선(Young-Sun Kim); 이태순(Tae-Soon Lee); 조성현(Sung-Hyun Cho); 이긍주(Geung-Joo Lee) (Weed & turfgrass science, 2017)
This study was conducted to evaluate the effect of liquid fertilizer containing humic acid (LFHA) on changes of creeping bentgrass quality and growth. Treatments were designed as follows; control fertilizer (CF), HA-1 ($CF+1ml\;m^{-2}LFHA$ LFHA), HA-2 ($CF+2ml\;m^{-2}LFHA$ LFHA), and HA-3 ($CF+4ml\;m^{-2}LFHA$). As compared with CF, soil chemical properties and chlorophyll content of clipping of LFHA treatments were not significantly different. Visual quality in both of HA-2 and HA-3 treatments was higher than that of CF treatment from September to November, and clipping yield on October 27. Shoot density, root length, and the content of nitrogen, phosphorus or potassium were increased by application of LFHA. The clipping yield was positively correlated with phosphorus content, potassium content or shoot density. Similarly, LFHA level was proportionate to clipping yield of creeping bentgrass, and N, P, K contents in the leaf tissue. These results generally demonstrated that the application of LFHA improved the growth and quality of creeping bentgrass by increase of N content or P in leaf tissue. 본 연구는 부식산 함유 액비(LFHA)의 시비에 따른 잔디의 생육과 품질의 변화를 평가하기 위해 수행하였다. 처리구는 대조구(CF), HA-1 ($CF+1ml\;m^{-2}LFHA$), HA-2 ($CF+2ml\;m^{-2}LFHA$), and HA-3 ($CF+4ml\;m^{-2}LFHA$)로 구분되었다. LFHA 처리 전후에 토양화학성은 차이를 나타내지 않았다. LFHA처리구와 대조구를 비교하였을 때, HA-2처리구와 HA-3처리구의 잔디 품질은 9월, 10월 및 11월 조사에서 높았고, 잔디예지물은 10월 27일 조사에서 증가하였다. 줄기 밀도, 뿌리 길이, 잎조직 내 질소, 인산 및 칼륨의 함량은 LFHA처리구에서 증가하였다. 잔디예지물은 잎 조직 내 인산 및 칼리함량이나 줄기 밀도와 정의 상관성을 보였고, 부식산 함유 액비는 잔디 밀도, 잔디예지물 및 잎조직 내 질소 및 인산함량과 각각 정의 상관성을 나타내었다. 이 결과들을 종합해 볼 때, 크리핑 벤트그래스에서 부식산 함유 액비의 시비는 잔디의 잎 조직 중 질소와 인산의 흡수가 증가하여 잔디예지물과 밀도가 증가하는 것을 확인 할 수 있었다.